2006
DOI: 10.1111/j.1464-410x.2006.06030.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two α1‐adrenoceptor antagonists, naftopidil and tamsulosin hydrochloride, in the treatment of lower urinary tract symptoms with benign prostatic hyperplasia: a randomized crossover study

Abstract: OBJECTIVES To compare the efficacy of two α1‐adrenoceptor antagonists, α1A‐adrenoceptor‐selective tamsulosin hydrochloride and α1D‐adrenoceptor‐selective naftopidil, in the treatment of lower urinary tract symptoms (LUTS) with benign prostatic hyperplasia (BPH). PATIENTS AND METHODS Thirty‐four patients (mean age 72.4 years, sd 4.3, range 66–79) with LUTS (International Prostate Symptom Score, IPSS >8) secondary to BPH were enrolled in a randomized crossover study. Seventeen patients were initially prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
128
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 19 publications
12
128
0
2
Order By: Relevance
“…1 The incidence and mortality of prostate cancer are still lower in Japan than in western countries, but both rates are rapidly increasing recently. Age-adjusted incidence and mortality of prostate cancer have risen from 7.1% in 1975 to 19.9% in 1998, and from 0.5% in 1950 to 8.6% in 2000. 2 In regard to treatment, organ-confined prostate cancer is curable with surgery or radiotherapy, but management of non-organ-confined disease fails in many cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The incidence and mortality of prostate cancer are still lower in Japan than in western countries, but both rates are rapidly increasing recently. Age-adjusted incidence and mortality of prostate cancer have risen from 7.1% in 1975 to 19.9% in 1998, and from 0.5% in 1950 to 8.6% in 2000. 2 In regard to treatment, organ-confined prostate cancer is curable with surgery or radiotherapy, but management of non-organ-confined disease fails in many cases.…”
mentioning
confidence: 99%
“…16 Several reports demonstrated that naftopidil improved bladder capacity and relaxed voiding via inhibition of afferent nerve activity, 17,18 and clinically improved not only obstructive voiding symptoms but also storage symptoms associated with BPH. 19,20 Kyprianou and Benning demonstrated that doxazosin and terazosin (quinazoline-derived a-1 adrenoceptor antagonists) had growth-inhibitory effects in human prostate cancer cell lines. 21 Doxazosin induced apoptosis in prostate cancer cells, although that action was independent of the capacity to antagonize a-1 adrenoceptors.…”
mentioning
confidence: 99%
“…Naftopidil is a derivative of arylpiperazine ether and a specific antagonist targeted for the adrenergic receptor [5], which has already been regarded as one of the most commonly utilized antagonists targeted for the adrenergic receptor to treat the benign prostatic hyperplasia (BPH) in Japan [6]. The arylpiperazine derivative mentioned in this paper is a subselective antagonist for BPH [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-over study comparing tamsulosin (α 1A -AR  α 1D -AR) with naftopidil (α 1D -AR  α 1A -AR), relief of storage symptoms was significantly better in subjects given naftopidil. 1,[51][52][53][54] However, this issue is still controversial and different results have been reported by other authors. 1,55,56 Recently, Kira and colleagues 57 studied the efficacy of silodosin in 85 patients with LUTS/BPH who were resistant to tamsulosin (n = 39) or naftopidil (n = 46), and reported a rapid and significant decrease in scores of decreased urinary stream and nocturia (both p  0.01), which were the most bothersome symptoms among IPSS.…”
Section: Dovepressmentioning
confidence: 93%